The professional development of adult education professors: A qualitative inquiry of the Kellogg faculty seminar participants - Li-Shyung Hwang (Adult Education Research Conference, 1996)
Qualitative research methods were used to focus on the professional development of adult education professors who participated in a Kellogg faculty seminar. Findings include a phenomenological understanding of the nature and significance of the participants’ professional development experiences.